Relationship Between Mindfulness and Affiliate Stigma in Parents of Children with Autism Spectrum Disorder in China: The Mediating Role of Coping Styles - Ya-Nan Wang; Qi-Heng Lin; Dan Meng; Jing Wang; Hai-Ping Xu; Wan-Hong Wei; Jin-Yan Zhang (Elsevier, 2024)
Purpose: This study aims to investigate the current status of affiliate stigma among parents of autistic children, analyze the influencing factors, explore the relationship among mindfulness, coping styles, and affiliate stigma, and verify the mediating role of coping styles between mindfulness and affiliate stigma in parents of children with autism in China. Method: Between February and April 2023, the Child Development Behaviour Centre of a public hospital in China recruited 345 parents of children with autism. These parents completed the general information questionnaire, the Mindful Attention Awareness Scale, the Affiliate Stigma Scale, and the Simple Coping Style Questionnaire. We then adapted the Hayes Process Macro and Bootstrap methods to examine the mediating effects of coping styles between mindfulness and affiliate stigma. Results: (1) The total affiliate stigma score of parents of children with autism was 48.53 (standard deviation:: 10.74). Parents' age, monthly family income, duration of care, mindfulness, and coping styles were the influencing factors of parental affiliate stigma. (2) Mindfulness was positively correlated with positive coping style (r = 0.33, p < .01) and negatively correlated with negative coping style, affiliate stigma (r = −0.38, −0.39, p < .01), whereas affiliate stigma was negatively correlated with positive coping style (r = −0.34, p < .01) and positively correlated with negative coping style (r = 0.41, p < .01). (3) Positive coping style and negative coping style play a parallel mediating role between mindfulness and affiliate stigma of parents of autistic children. Conclusions: Parents of children with autism experience significant levels of affiliate stigma. Mindfulness has a direct impact on associated stigma in parents of children with autism and also indirectly predicts associated stigma through the intermediary influence of positive and negative coping styles. Healthcare professionals could perform mindfulness interventions from an optimistic psychology viewpoint to boost parents' mindfulness and coping abilities, thereby accomplishing the objective of mitigating affiliate stigma.